An Economic Study of the Most Important Varieties of Wheat Crop in Kafr El-Sheikh Governorate, Egypt - Shehata, Gaber A. B.; Al-Tarawi, Abdel-Sattar; Al-Damiri, Mohamed (Advances in Social Sciences Research Journal, 2022)
The agricultural sector represents an important place in the national economy, as it contributes about LE 438.73 billion, representing about 11.31% of the national income, which amounted to about LE 3879.42 billion in 2020, and the cultivated area of the wheat crop in Egypt reached 3.13 million feddans, while the cultivated area in Kafr El-Sheikh Governorate amounted to about 217.11 thousand feddans in 2019. The research problem is represented in the food production of the wheat crop that does not meet the food consumption needs of it as a result of the steady increase in the population, which led to the emergence of a food gap that is covered by importing from abroad. The research aims to shed light on some economic indicators for the production of wheat crop in Kafr El-Sheikh Governorate and to estimate the economic efficiency of the production elements used, by relying on the method of descriptive and quantitative analysis of data using standard analytical methods, and the research relied on two types of published and unpublished secondary data in addition to primary data for a sample. A field survey was collected using a research questionnaire specially prepared for this purpose, with a personal interview from a multi-stage random sample of wheat growers in Kafr El-Sheikh Governorate, and with regard to the productive situation of the most important varieties of wheat crop in Egypt and Kafr El-Sheikh, the most important results were as follows: The average area of wheat in Egypt during the period (2005-2019) was about 3.02 million feddans, and the average feddan productivity of wheat in Egypt during the period (2005-2019) was about 18.29 ardeb/ feddan, and the average total production was about 55.21 million ardeb Which is equivalent to about 8.142 million tons, while the average cultivated area in Kafr El-Sheikh Governorate during the same period was about 230.43 thousand feddans. With an average relative importance of the cultivated area of wheat in Kafr El-Sheikh Governorate compared to the cultivated area of it in Egypt, it turned out that it amounted to about 7.67%, and it was found that the average productivity per feddan of wheat in Kafr El-Sheikh during the period (2005-2019) amounted to about 15.51 ardeb/ feddan, and the average of total production is about 3.58 million ardebs, which is equivalent to about 537 million tons. By studying the average relative importance of the total production of wheat in Kafr El-Sheikh Governorate compared to the total production of wheat in Egypt, it was found that it amounted to about 6.35%. It is also clear that the value of the cost of production inputs, as well as the relative importance of each of them to the total costs of wheat varieties (Misr 1, Misr 2, Giza 171) in question, where the average total costs of them amounted to about LE 12,820, 12.04 and 10.55 thousand/ feddan for each of them, respectively, and the average of the fixed costs are about LE 5.6, 4.78, and 5.69 thousand / feddan for each of them, respectively, representing about 43.77%, 39.7% and 53.9% of the average total costs, and the average public expenses amounted to about LE 40.76, 90.19 and 75.32 / feddan, representing about 0.32 %, 0.75%, 0.71% of each, respectively, of the average total total costs. The production functions were estimated in the logarithmic form, and they gave the best results in order to estimate the economic efficiency used in the production of wheat varieties, thus activating the positive factors and discouraging negative factors to reach a better use of the productive resources used in the production of this crop. The cubic model was chosen, and the optimum and maximal size of the profits were estimated for each of the wheat varieties, Misr 1, Misr 2, and Giza 171, while the variable costs amounted to about LE 7.2, 7.26 and 4.86 thousand/ feddan for each of them, respectively. The economic indicators for the production of the most important varieties of wheat grown in Kafr El-Sheikh Governorate were studied, which are the varieties of Misr 1, Misr 2, and Giza 171. The problems faced by wheat farmers in the research sample were also studied, and the opinions of farmers in these problems were studied.